Implementasi Algoritma RC4+ dan Metode Spread Spectrum Untuk Mengamankan Pesan Rahasia Kedalam Citra Digital - Zalukhu, Otriyani Erwandy (TIN: Terapan Informatika Nusantara, 2021)
The current development of information technology is soaring widely that it is very easy to exchange data or information. On the other hand, there will be many data security problems committed by irresponsible people by means of wiretapping, destroying, stealing, falsifying data, or by other means. Cryptographic techniques and steganography are two tools that offer data security. Cryptography guarantees the confidentiality, authenticity and integrity of data while steganogafi aims to hide and retrieve data. The RC4 + algorithm is a variation of the RC4 asymmetric algorithm, which uses only one key to perform the encryption and decryption process. The spread spectrum method is a strategic method that is often used to protect copyright on digital products by means of random messages. This study describes the security of secret messages in the form of digital images by combining two security techniques. Where RC4 + aims to maintain the authenticity of data by means of encryption and decryption processes, while the spread spectrum method serves to maintain the integrity of the copyright of the digital image message. Based on the results of tests carried out with the RC4 + algorithm with encryption and decryption processes as well as the spread spectrum method in the Matlab application that was made to run well in accordance with the initial design. The two security methods used ensure the integrity of the data or information until it reaches the hands of the recipient of the secret message.